Complex regional pain syndrome following a centipede bite: a case report - Suthimon Thumtecho (2020)
© 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group. Context: Complex Regional Pain Syndrome (CRPS) is a chronic neuropathic pain condition associated with autonomic features. To date, the development of CRPS following centipede bite has not been reported. We report a case of CRPS likely secondary to a centipede bite. Case details: A 31-year-old female was bitten by a centipede on the right 2nd toe. She was initially treated with analgesics, and two weeks later developed severe pain, allodynia, pruritus, and edema of the right foot, with hyperpigmentation over the affected toe. The X-ray, ultrasound, electromyography, nerve conduction velocity studies of the foot, blood chemistries, and erythrocyte sedimentation rate showed no abnormalities. The patient was diagnosed with CRPS type 1 by fulfilling the Budapest criteria. She was treated with gabapentin, amitriptyline, desloratadine, and fluoxetine, along with physical rehabilitation. Clinical symptoms gradually improved, and resolved at approximately 9 months with persistent hyperpigmentation. Discussion: Centipede bite may be an eliciting event for CRPS. It is unknown whether direct bite trauma or envenomation was the primary etiology in this case. Awareness of this condition is important for early diagnosis and appropriate management.